The development of a modified comprehensive geriatric assessment for use in the emergency department using a RAND/UCLA appropriateness method. (March 2021) - Taylor, Andrea; Broadbent, Marc; Gurung, Apil; Wallis, Marianne
Highlights: CGA in the ED is considered useful for older adults yet is difficult to complete. A RAND/UCLA consensus methodology has been applied to develop a unique CGA for ED use. The CGA satisfies the unique work-flow conditions found in the ED. Abstract: Background: The universal screening and comprehensive assessment of older persons presenting to the emergency department is considered useful, yet is difficult to embed. A number of assessment instruments exist however they are not widely used and there is a lack of agreement between clinicians as to which tools are best suited to the emergency department. The aim of this study was to develop a modified comprehensive geriatric assessment using consensus methodology for use by the multidisciplinary team in the emergency department. Method: The modified comprehensive geriatric assessment was formulated using the RAND/UCLA appropriateness methodology incorporating consensus opinion from an expert group of clinicians and the best scientific evidence available. A series of pre and post survey and expert group meetings were held with expert multidisciplinary clinicians. Emphasis was placed on a pragmatic approach to the development of a document which reflected consensus opinion. Results: Between nine and 15 expert group members participated in the stages of the process. A tiered approach incorporating different aspects of screening and/or assessments was considered optimal to reflect the stages of decision-making in the emergency department process. Conclusion: A unique approach to the screening and assessment of the frail older person was developed using consensus methodology to develop a modified comprehensive geriatric assessment for use in the emergency department. Associated actions and interventions are an important next step, with pilot site testing.